2010
DOI: 10.3354/meps08489
|View full text |Cite
|
Sign up to set email alerts
|

Bycatch reduction device conserves diamondback terrapin without affecting catch of blue crab

Abstract: Bycatch mortality of non-target species in fisheries is a major threat to the conservation and restoration of marine and estuarine species. Attempts to reduce bycatch by fitting fishing gear with excluder devices have typically been met with resistance due to reductions in catch of target species. We examined the possibility that conservation and fishery goals could be met simultaneously. In lower Chesapeake Bay, we tested a mechanism for reducing bycatch of diamondback terrapin Malaclemys terrapin in blue-cra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…) or remain until the trap is hauled (Rook et al . ). In some cases, changes to the material have allowed organisms to detect and avoid the gear altogether (Trippel et al .…”
Section: Reviewmentioning
confidence: 97%
“…) or remain until the trap is hauled (Rook et al . ). In some cases, changes to the material have allowed organisms to detect and avoid the gear altogether (Trippel et al .…”
Section: Reviewmentioning
confidence: 97%
“…A chi-square test (χ 2 test, p ≥ 0.05) was used to investigate possible differences among averages of CPUE per trap type. Bycatch and discard species collected were also quantified (CPUE) to explore possible effects of trap types in competition and predation of the target species as a contribution to the development of an ecological approach to the fishery (García-Rodríguez et al 2000, Rook et al 2010.…”
Section: Evaluation Of Trapsmentioning
confidence: 99%
“…It is generally accepted that males and juvenile females are more vulnerable to crab-trap mortality than are adult females (Roosenburg et al 1997;Roosenburg and Green 2000;Gibbons et al 2001;Butler and Heinrich 2007;Dorcas et al 2007;Hart and McIvor 2008;Rook et al 2010;Wolak et al 2010;Coleman et al 2011;Hart and Crowder 2011;Baxter 2013). However, Roosenburg (2004) suggested that regional studies should determine which sex and life-history stages are susceptible to crab-trap mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that BRDs reduce terrapin bycatch while not significantly depressing blue crab catch (Mazzarella 1994;Roosenburg et al 1997;Cuevas et al 2000;Roosenburg and Green 2000;Butler and Heinrich 2007;Rook et al 2010;Hart and Crowder 2011;Morris et al 2011;Baxter 2013;Upperman et al 2014), perhaps even increasing it (Wood 1997;Guillory and Prejean 1998). Guillory and Prejean (1998) suggested that BRDs might provide rigidity to funnel openings, thus reducing crab egress.…”
Section: Discussionmentioning
confidence: 99%